Modelling of high performance electrocoalescer based on experimental data - Редріх Олегович Путятін; Віталій Степанович Цапар (Вісник Національного технічного університету України «Київський політехнічний інститут імені Ігоря Сікорського»: Серія «Хімічна інженерія, екологія та ресурсозбереження», 2023)
Modern approaches to automatic control of crude oil dewatering and desalting are predominantly model-free, and described model-based systems lack precise mathematical description. Not a single research provides a dynamic input-output model for electric dehydrator, suitable for control system development. As far as electric dehydrator, which is the main plant to control in the process, is a non-linear system with distributed parameters, a need for linearization arises. The aim of present study is to compare different methods for obtaining approximate transfer function of an electric dehydrator from graphical experimental data.